ANALYSIS OF MSME BUSINESS PERFORMANCE IN THE ERA OF INDUSTRIAL REVOLUTION 4.0: CASE STUDY ON MSME IN THE CULINARY SECTOR - Setyawati, Amelia; Mustikarini, Carolina Novi; Kusuma, Rr. Chusnu Syarifa Diah; Seseli, Eka Merdekawati Imelda (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
Implementing innovation by MSME actors can be done by improving the quality of products or services, for example, by improving the production process or using more efficient technology to increase productivity and business effectiveness. The research aims to analyze the influence of innovation capability and technological innovation on business performance. The sample in this study consisted of 90 respondents from MSME actors in the culinary sector in Indonesia who were determined using a convenience sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis uses the SPSS application by displaying data processing results through testing research instruments with validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, it is stated that innovation capability and technological innovation have a positive and significant effect on business performance. The research implications suggest that this research provides theoretical insights and practical views that can help MSMEs in the culinary sector in making strategic decisions. The implications of this research can help MSMEs improve their innovation capabilities, optimize the use of technology, and ultimately improve their overall business performance.